TEROBOSAN BARU MENGURANGI CYBERBULLYING: KONSELING KELOMPOK CBT DENGAN TEKNIK SELF-CONTROL - Dora Anggela; I Wayan Dharmayana; Mayang T. Afriwilda (UNIVERSITAS BENGKULU, 2025)
This study aims to examine the effectiveness of group counseling services based on Cognitive Behavior Therapy (CBT) with the self-control technique in reducing students' cyberbullying behavior. The study employed an experimental method with a two-group pre-test post-test control design. The population of the study consisted of 55 students from the XI Marketing class at SMK Negeri 1 Kota Bengkulu. A total of 10 students were selected as the sample, consisting of 5 students in the control group and 5 in the experimental group, chosen through purposive sampling. Data were collected using a questionnaire with a Likert scale model and analyzed using the paired sample t-test. The results showed that the experimental group experienced a significant decrease in the average score of cyberbullying behavior from 159.6 (pre-test) to 91 (post-test). Conversely, the control group also showed a decrease, but it was less substantial, from 161.2 (pre-test) to 149.6 (post-test). The t-test analysis revealed that the decrease in the experimental group (68.6) was significantly greater than in the control group (11.6). Therefore, it can be concluded that group counseling services based on Cognitive Behavior Therapy (CBT) with the self-control technique are effective in reducing students' cyberbullying behavior.Keywords: Cyberbullying Behavior, Group Counseling CBT, Self-Control Technique